Neuronal Mitochondria Modulation of LPS-Induced Neuroinflammation - Harland, Micah; Torres, Sandy; Liu, Jingyi; Wang, Xinglong (The Journal of neuroscience, 2020)
Neuronal mitochondria dysfunction and neuroinflammation are two prominent pathological features increasingly realized as important pathogenic mechanisms for neurodegenerative diseases. However, little attempt has been taken to investigate the likely interactions between them. Mitofusin2 (Mfn2) is a mitochondrial outer membrane protein regulating mitochondrial fusion, a dynamic process essential for mitochondrial function. To explore the significance of neuronal mitochondria in the regulation of neuroinflammation, male and female transgenic mice with forced overexpression of Mfn2 specifically in neurons were intraperitoneally injected with lipopolysaccharide (LPS), a widely used approach to model neurodegeneration-associated neuroinflammation. Remarkably, LPS-induced lethality was almost completely abrogated in neuronal Mfn2 overexpression mice. Compared with nontransgenic wild-type mice, mice with neuronal Mfn2 overexpression also exhibited alleviated bodyweight loss, behavioral sickness, and myocardial dysfunction. LPS-induced release of IL-1β but not TNF-α was further found greatly inhibited in the CNS of mice with neuronal Mfn2 overexpression, whereas peripheral inflammatory responses in the blood, heart, lung, and spleen remained unchanged. At the cellular and molecular levels, neuronal Mfn2 suppressed the activation of microglia, prevented LPS-induced mitochondrial fragmentation in neurons, and importantly, upregulated the expression of CX3CL1, a unique chemokine constitutively produced by neurons to suppress microglial activation. Together, these results reveal an unrecognized possible role of neuronal mitochondria in the regulation of microglial activation, and propose neuronal Mfn2 as a likely mechanistic linker between neuronal mitochondria dysfunction and neuroinflammation in neurodegeneration. SIGNIFICANCE STATEMENT Our study suggests that Mfn2 in neurons contributes to the regulation of neuroinflammation. Based on the remarkable suppression of LPS-induced neuroinflammation and neurodegeneration-associated mitochondrial dysfunction and dynamic abnormalities by neuronal Mfn2, this study centered on Mfn2-mediated neuroinflammation reveals novel molecular mechanisms that are involved in both mitochondrial dysfunction and neuroinflammation in neurodegenerative diseases. The pharmacological targeting of Mfn2 may present a novel treatment for neuroinflammation-associated diseases.